2015
DOI: 10.1038/srep17203
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional direct cell patterning in collagen hydrogels with near-infrared femtosecond laser

Abstract: We report a methodology for three-dimensional (3D) cell patterning in a hydrogel in situ. Gold nanorods within a cell-encapsulating collagen hydrogel absorb a focused near-infrared femtosecond laser beam, locally denaturing the collagen and forming channels, into which cells migrate, proliferate, and align in 3D. Importantly, pattern resolution is tunable based on writing speed and laser power, and high cell viability (>90%) is achieved using higher writing speeds and lower laser intensities. Overall, this pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 28 publications
1
61
0
Order By: Relevance
“…For friction welding, the low efficiency and welding defects are concerning. Alternatively, highpower-density laser has attracted enormous research interest and found its wide application in a broad branch of manufacturing areas including selective laser sintering and three-dimensional printing [1][2][3][4][5][6], surface nanostructuring [7][8][9][10][11][12], multimaterial joining and integration [13][14][15][16][17], material removal [18,19], and mechanical/optical property enhancements [20][21][22][23]. Characteristics, such as contact-free processing, good flexibility and tunablity, high efficiency, and throughput, make laser a feasible route for welding of 42CrMo [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…For friction welding, the low efficiency and welding defects are concerning. Alternatively, highpower-density laser has attracted enormous research interest and found its wide application in a broad branch of manufacturing areas including selective laser sintering and three-dimensional printing [1][2][3][4][5][6], surface nanostructuring [7][8][9][10][11][12], multimaterial joining and integration [13][14][15][16][17], material removal [18,19], and mechanical/optical property enhancements [20][21][22][23]. Characteristics, such as contact-free processing, good flexibility and tunablity, high efficiency, and throughput, make laser a feasible route for welding of 42CrMo [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Subtractive patterning was also achieved by exploiting thermal degradation of materials. Using a near-infrared femtosecond laser, Hribar et al controlled the thermal denaturation of cell-populated collagen-gold nanorod composites, thus creating channels with diameters down to~8 μm, whilst maintaining good cell viability [98].…”
Section: Hydrogel Engineeringmentioning
confidence: 99%
“…This makes the approach particularly well suited for the optimization of the test parameters. The small changes in sample composition across gradient samples have been found to affect cellular attachment [90,92,[94][95][96][97], viability [27,64,72], migration [66,69,70,[98][99][100] and differentiation [71][72][73]83,[101][102][103][104]. To demonstrate this phenomena, Figure 2 shows a study of the effects of a Young's modulus gradient on human chondrocyte glycosaminoglycan content.…”
Section: Gradient Samplesmentioning
confidence: 99%
See 2 more Smart Citations